Review on the methodology to assess respiratory tract lesions in pigs and their production impact - Maes, Dominiek; Sibila, Marina; Pieters, Maria; Haesebrouck, Freddy; Segalés, Joaquim; de Oliveira, Luís Guilherme [UNESP] (Springer Nature, 2023)
Porcine respiratory disease is one of the most important health problems in pig production worldwide. Cranioventral pulmonary consolidation (CVPC) and pleurisy are the two most common lesions in the respiratory tract of slaughtered pigs. The present review paper discusses pathogens involved in the lesions, lesion prevalence, scoring systems, advantages and disadvantages of slaughterhouse examination, and the impact of CVPC and pleurisy on performance, carcass, and meat quality. Cranioventral pulmonary consolidation and pleurisy in slaughter pigs are characteristic for infections with Mycoplasma hyopneumoniae and Actinobacillus pleuropneumoniae, respectively, although other pathogens may cause similar lesions and/or be involved in their development. The overall prevalence of CVPC and pleurisy in slaughter pigs are still high, being the prevalence of CVPC generally higher than that of chronic pleurisy. The advantages and disadvantages of slaughterhouse examination are discussed in relation to practical aspects, the assessment of lesions, the number and representativeness of the examined animals and the interpretation and value of the results for the stakeholders. The main scoring methods for CVPC and pleurisy are shortly reviewed. In general, scoring methods can be applied rapidly and easily, although significant variation due to abattoir and observer remains. Artificial intelligence-based technologies that automatically score lesions and facilitate processing of data may aid solving these problems. Cranioventral pulmonary consolidation and pleurisy have a major negative impact on pig performance, and the effects increase the extension of the lesions and/or presence of multiple lesions. The performance losses caused by these lesions, however, vary significantly between studies and farms, possibly due to differences in study population and used methodology. Both lesions also have a negative impact on different carcass and meat quality parameters, leading to increased risk for poor processing and storage of the carcasses. Monitoring lung lesions of slaughter pigs should be optimized and implemented routinely; however, it is recommended to complement this information with farm data and laboratory results for specific pathogens.
Keywords: cranioventral pulmonary consolidation; impact; lesion; lung; Pigs; pleurisy; slaughterhouse